A green and reliable communication modeling for industrial internet of things. (February 2017) - Liu, Anfeng; Zhang, Qi; Li, Zhetao; Choi, Young-june; Li, Jie; Komuro, Nobuyoshi
Highlights: An improved protocol (HTP) is proposed through combining SW-ARQ and NCRT scheme. HTP protocol is a strategy which can optimize multiple performances at the same time. HTP protocol is proved to improve lifetime above 15% under same reliability. HTP protocol is proved to improve reliability by 10%–45% under same lifetime. HTP protocol is more practicality which allows low complexity implementation. Abstract: Green and reliable communication has great significance for Industrial Internet of Things. Unfortunately, because of the loss nature, achieving reliable transmission is challenging. In this paper, a novel hybrid transmission protocol (HTP) is proposed to maximize lifetime while the reliability is still guaranteed. The proposed protocol adopts Send-Wait automatic Repeat-Request protocol in hotspot areas to reduce the energy consumption and network coding based redundant transmission approach with adaptive redundancy level in non-hotspot areas to guarantee the reliability. The proposed protocol could improve the lifetime and shorten the delay on the premise of ensuring the reliability. Comparing with Send-Wait automatic Repeat-Request protocol, it can improve lifetime by 15%–30% under the same reliability and improve the reliability by 12%–45% under the same lifetime. Comparing with network coding based redundant transmission approach, the lifetime has increased by more than one time under the same reliability. Graphical abstract: